Level of economic enterprise management competency of elected local officials in Anahawan and Hinundayan, Southern Leyte. - Abad, Ma. Imelda O. (Ma. Imelda Abad [and] Jane P. Victoria, 2010)
The Local Government Units (LGUs) are responsible for the proper management of "local public enterprises" (LPEs). These economic enterprises should be self-sustaining and should be able to generate incomes to cover administration and operations expenses; however, oftentimes these economic enterprises operate at a loss. The success and failure of some LGUs to sustain and maintain LPEs supports the need for conducting a research on the Level of Economic Enterprise Management Competency of Local Government Officials.